Does human capital shortage cause inequality? Evidence from Turkish provinces - Aksoy, Tolga; Gonel, Feride (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2016)
The aim of this paper is to investigate the impact of human capital on regional income inequality which is one of the most serious problems of Turkey causing political and economic instability. To this end, a conditional convergence model based on real per capita gross value added and labour force with different education levels is estimated using the panel data set of Turkish regions for the time period 2004-2011. Results reveal that labour force with high and vocational high school education and above high school education contribute to increase in regional inequality, while labour force with less than high school education has no effect.
Keywords: Regional inequality; human capital; economic growth; REGIONAL CONVERGENCE; ECONOMIC-GROWTH; PRODUCTIVITY; EDUCATION; INCOME; Business & Economics